The "Scroll, Checkout, Repeat" Phenomenon from a Hadith Perspective: A Thematic Study of the Concepts of Israf and Consumption Control - Mohammad Yusuf Zakaria; Vivin Nurfaida; Muhid Muhid (Journal of General Education and Humanities, 2026)
The rapid expansion of e-commerce has generated a cyclical pattern of impulsive digital consumption widely characterized as "scroll, checkout, repeat," in which purchasing decisions are driven by algorithmic stimuli, Fear of Missing Out (FOMO), and hedonic shopping lifestyle rather than genuine need. Despite growing scholarly attention to Islamic consumer ethics, prophetic hadith has rarely been positioned as the primary analytical framework for addressing this phenomenon. This study analyzes the scroll, checkout, repeat phenomenon through the lens of prophetic hadith, focusing on the concepts of israf and consumption control. A qualitative library research design was employed, using the thematic hadith method (maudhu'i). The corpus consisted of six core hadith drawn from the five canonical collections of Sahih al-Bukhari, Sahih Muslim, Sunan al-Tirmidhi, Sunan Ibn Majah, and Musnad Ahmad, all classified as sahih or hasan based on isnad verification cross-checked against classical syarah commentaries. Findings show that israf operates across behavioral, psychological, and moral-spiritual dimensions, while prophetic consumption control encompasses quantitative sufficiency, attentional discipline, and inner contentment (qana'ah). These principles can be conceptually related to key empirical drivers of digital impulsive buying, though this normative-conceptual study does not empirically test the framework against consumer data.